Promoting and Playing football during the War. The International Federation of Association Football, the Axis Power and the Second World War - Vonnard, Philippe; Quin, Grégory (Hispania Nova, 2019)
The repercussions of the rise of totalitarianism in the interwar period and more precisely of the war itself on international sport have already been the subject of detailed studies, particularly around the International Olympic Committee (IOC), but football - and in particular the Fédération Internationale de Football Association (FIFA) - is also an excellent analyst of this "turning point" in the history of the 20th century. Indeed, the 1930s and 1940s were key decades to understand the challenges of the politicization of football, to highlight how sports leaders operate in an ambivalent context, but also to analyse the transformation of the governance of an international organization between the attempts of interference driven by Axis forces and the "resistance" orchestrated by Secretary General. Thus, this article aims to question and analyse the investment of Axis forces around FIFA, particularly in the light of its continued activity during the war, using some original archives and documents from the FIFA documentation center.
Keywords: History; Second World War; Politics; FIFA; International Relations